METODOLOGIA DE PUNERE ÎN PRACTICĂ A GEOREFERENŢIERII UTILIZÂND TRANSFORMAREA AFINĂ (PANGEEA, 2025)
Georeferencing is the process of converting a image in file coordinates or page coordinates to a file in map coordinates in a specific map project, coordinate system, map projection and datum. For example, a scanned map can have an origin point and a raster association where each point on the map is identifiable by it's file coordinates. In order to georeference an image, you need to identify map coordinates of any 3 points on the map. There are two main methods of registration: one method is to manually type in map coordinates for points, then select those points on your image, another method is to bring upa coverage that is registered and that has features in it that are visible in the scanned file to register.